Proteins and peptides as antigen candidates for the immunodiagnosis of hepatitis D - Sandra Rodrigues Xavier; Isabelle Caroline dos Santos Barcelos; Isadora Braga Gandra; Sabrina Paula Pereira; Anna Julia Ribeiro; Kamila Alves Silva; Carlos Ananias Aparecido Resende; Lucas da Silva Lopes; Rafaela Camargo Rodrigues Machado; Leonardo Maciel Santos Silva; Líria Souza Silva; Lívia Corrêa Ferreira; et al. (Amino Acids)
Abstract Designing innovative, accurate, universal, and accessible diagnostic tests is mandatory to improve screening, prevention, and management of hepatitis D (HD), especially in endemic areas with poor infrastructure and restricted access to public health care. Recombinant proteins (RP), recombinant multiepitope proteins (RMP), and synthetic peptides have been extensively reported as tools for efficient immunodiagnosis of several diseases. This review aimed to discuss the use of these antigens for the immunodiagnosis of HD. To this end, a bibliographic study was conducted in the PubMed database by searching the primary (“Hepatitis D” and “Hepatitis Delta”), secondary (“Detection”, “Diagno*”, “Diagnosis”, “Immunodiagnosis”, and “Serodiagnosis”), and tertiary (“Chimera”, “Epitope”, “Peptide”; “Protein” and “Recombinant”) descriptors, including papers published up to January 2025. Review articles and case reports were excluded. Only nine articles (five for RP, three for synthetic peptides, and one for RMP) met the inclusion criteria, revealing that there are very few studies on this subject, particularly when compared to the advances made in the diagnosis of hepatitis A, B, and C. Despite the scarcity of articles published in the literature, six of the nine analyzed studies corroborate the potential of these antigens to effectively replace traditional diagnostic methods, including development of rapid tests. These data highlight the need for further studies to assess the potential of RP, RMP, and synthetic peptides for immunodiagnosis of HD, aiming to increase the accuracy of diagnosis, as well as improve monitoring and prevention.